Hum - Phillips, Helen, 1981- (Marysue Rucci Books, 2024)
"After losing her job to artificial intelligence, May, in a city populated by intelligent robots called "hums," takes her family on a three-night respite to the Botanical Garden, a rare green refuge, where her children come under threat and she is forced to trust a hum to save them"--